Analysis of Liquid Loading and Sandness in Gas Wells A1, A2 And Their Correction with The Plunger Lift Method in Field B - Ali Musnal; Richa Melysa (Universitas Islam Riau (UIR) Press, 2023)
The inability of the gas to lift liquid to the surface causes liquid to accumulate in the downhole, this event is called liquid loading, and sand deposits at the bottom of the well are caused to be swept away by the gas flow. If a well has liquid loading and sandification, well production will decrease and even the well will die. For this reason, it is necessary to carry out a predictive analysis of the well and a method to overcome the problem of liquid loading and sandiness using a plunger lift.Liquid loading is not always easy to identify, because the well is still producing significantly. The method used in the petroleum world to identify liquid loading is the